2008
DOI: 10.1111/j.1447-0756.2008.00792.x
|View full text |Cite
|
Sign up to set email alerts
|

ACE and MTHFR gene polymorphisms in unexplained recurrent pregnancy loss

Abstract: In conclusion, the present study reveals lack of association of MTHFR C677T and ACE I/D polymorphisms in RPL in South Indian women. However, we cannot exclude the possibility that other polymorphisms of ACE and MTHFR genes could be associated with the disease and might be clinically useful as a marker to assess risk for RPL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 23 publications
2
31
1
Order By: Relevance
“…[45][46][47][48][49][50][51][52] The c.1286A→C variant has been studied less, but current evidence suggests that it is milder than the "thermolabile" variant. [53][54][55][56] Preliminary findings in combined genotypes have found that they are not significantly different from controls.…”
Section: Acmg Practice Guidelinesmentioning
confidence: 99%
“…[45][46][47][48][49][50][51][52] The c.1286A→C variant has been studied less, but current evidence suggests that it is milder than the "thermolabile" variant. [53][54][55][56] Preliminary findings in combined genotypes have found that they are not significantly different from controls.…”
Section: Acmg Practice Guidelinesmentioning
confidence: 99%
“…Smallest sample size was 24 [41] and largest sample size was 329 [50]. Seven studies did not show any association between C677T polymorphism and RPL risk [21,28,29,37,43,47,52], remaining twenty-two studies showed significant association. In twenty-nine studies, total cases were 3725 with CC (1971), CT (1325) and TT (429), and controls were 4105 with CC (2545), CT (1218), and TT (342).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 92%
“…Another 24 articles from remaining 53 articles were again excluded because studied population was not Asian. Finally, 29 studies were included in present meta-analysis [11,15,16,21,[27][28][29][30] (Fig. 1; Table 1).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations